Allergic bronchopulmonary aspergillosis in a patient with ankylosing spondylitis treated with adalimumab. Issue 8 (23rd June 2021) - Suzuki, Yudai; Takasaka, Naoki; Matsubayashi, Sachi; Kojima, Ayako; Shinfuku, Kyota; Hasegawa, Tsukasa; Yamada, Masami; Fujisaki, Ikumi; Seki, Aya; Seki, Yoshitaka; Ishikawa, Takeo; Kuwano, Kazuyoshi
Abstract: We herein report a case of allergic bronchopulmonary aspergillosis (ABPA) that occurred in a man treated with adalimumab for ankylosing spondylitis (AS). A 69‐year‐old man with a history of ankylosing spondylitis treated by adalimumab, an anti‐tumour necrosis factor‐α (TNF‐α) antibody, developed cough and wheezing. Chest computed tomography showed obstruction of dilated left upper lobe bronchus by high attenuation mucus as well as central bronchiectasis. Both Aspergillus ‐specific immunoglobulin E (IgE) and Aspergillus precipitating antibody were positive and Aspergillus fumigatus was detected in a sputum culture. According to the new diagnostic criteria, the patient was diagnosed with ABPA. His condition rapidly improved after the withdrawal of adalimumab and initiation of prednisolone and itraconazole. Anti‐TNF‐α antibody might cause ABPA through both aggravation of the host's T‐helper 2 immunological response and anti‐fungal response. Abstract : We report a case of allergic bronchopulmonary aspergillosis (ABPA) that occurred in a man receiving adalimumab for ankylosing spondylitis. This case suggests that anti‐tumour necrosis factor‐α (TNF‐α) antibody might cause ABPA in terms of disruption of the Th2/Th1 balance and the anti‐fungal response.